2014
DOI: 10.18801/jbar.010114.05
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic correlation co-efficient of quantitative characters and character association of aromatic rice

Abstract: An experiment was conducted in research fields under the Department of Genetics and Plant Breeding of Bangabandhu Sheikh Mujibur Rahman Agricultural University in Bangladesh to study Phenotypic and genotypic correlation coefficient of quantitative characters and character association of aromatic rice. Forty-one aromatic rice germplasm of diverse sources were used to assess the character association and contribution of characters towards grain yield. Path coefficient analyses were carried out for selected genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
23
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 4 publications
9
23
1
1
Order By: Relevance
“…The phenotypic correlation between spikelet sterility status (%) vs. spikelet fertility status(%) were negative and significant at1 % level. The results are in agreement with Karim et al (2014) for 1000 grain weight and spikelet sterility status(%). Pleiotrophy and/or linkage may also be genetic the reason for this type of negative association.…”
Section: Resultssupporting
confidence: 86%
“…The phenotypic correlation between spikelet sterility status (%) vs. spikelet fertility status(%) were negative and significant at1 % level. The results are in agreement with Karim et al (2014) for 1000 grain weight and spikelet sterility status(%). Pleiotrophy and/or linkage may also be genetic the reason for this type of negative association.…”
Section: Resultssupporting
confidence: 86%
“…Number of filled grain per panicle showed a positive strong to moderate correlation with number of total grain per panicle (r p =0.951**) and biomass yield (r p =0.466**), respectively. However, contrary to the observation of Karim et al (2014) who reported highly significant negative correlation between 1000-grains weight and number of filled grain per panicle. According to Adams and Grafius (1971), the negative correlations arise primarily from competition for a common possibility, such as nutrient supply.…”
Section: Phenotypic Correlation Between the Traitscontrasting
confidence: 94%
“…Mulugeta (2015) reported biomass yield and plant height as the major contributors to yield and had direct effect on yield in upland rice. Karim et al (2014) and Kishore et al (2015) reported that plant height had high direct positive effect on yield. On the other hand, days to heading (-0.020), days to maturity (-0.068), panicle length (-0.062), culm length (-0.580), unfilled grains per panicle (-0.257), filled grains per panicle (-0.503) and thousand grains weight (-0.049) had negative direct loading on yield except on culm length, panicle length, and thousand grains weight but showed positive and significant genotypic correlation with yield.…”
Section: Direct Effect Of Different Traits On Yieldmentioning
confidence: 99%
“…Whereas the control had a mean grain weight of 2.89 g, superior mutant families presented a mean value of 4.40 g. This result observed in these mutants can be related to a greater yield, since the grain mass is a major component of yield (Jeng et al 2006;Song et al 2007;Hasan et al 2013;Karim et al 2014). It is worth emphasizing that this increase in the main panicle grain weight will be relevant provided that there is no reduction in other components of grain yield.…”
Section: Vk Luz Et Almentioning
confidence: 86%